Shrapnel in carotid sheath: A rare penetrating neck injury - Muhammad Rehan; Savera Anwar; Hadia Wali; Aysha Noor; Omer Ehsan; Shayan Shahid Ansari (Chinese Journal of Traumatology)
Injuries deeper than the platysma are considered as penetrating neck injuries, constituting approximately 5% – 10% of all trauma. Many vital organs are at risk from a penetrating neck injury. These injuries in zone 1 have the highest mortality, because the injuries are close to the vital organs and difficult to access surgically. A 41-year-old male, a car mechanic by profession, presented to the emergency department with a penetrating neck injury on the right side. CT scan demonstrated a metallic foreign body in zone 1 between the right internal jugular vein and the common carotid artery. The patient was asymptomatic, and the foreign body was removed surgically. This case shows a rare presentation of a penetrating neck injury with a foreign body located in zone 1, where no vital internal structure was injured. As of now, no previous case report has been identified on such presentation. Thus, it will provide a valuable addition to the pre-existing literature.